Revising the global multidimensional poverty index: Empirical insights and robustness - Alkire, S; Kanagaratnam, U; Nogales, R; Suppa, N (Oxford Poverty and Human Development Initiative (OPHI), 2020)
The global Multidimensional Poverty Index, published annually since 2010, captures acute multidimensional poverty in the developing regions of the world. In 2018, five of its ten indicators were revised with the purpose of aligning the index to the SDGs insofar as current data permit. This paper provides comprehensive analyses of the consequences of this revision from three perspectives. First, we offer new empirical insights available from the revised specification. Second, we analyse its robustness to changes in some key parameters, including the poverty cutoff and dimensional weights. Third, we compare the revised and the original specifications by implementing both on the same 105 national datasets. The country orderings in the revised specification are found to be robust to plausible parametric alternatives. Largely, these country orderings are at least as robust as the original one. Additional research on robustness standards is suggested.